2006
DOI: 10.1900/rds.2006.3.178
|View full text |Cite
|
Sign up to set email alerts
|

Stevioside Counteracts Beta-Cell Lipotoxicity without Affecting Acetyl CoA Carboxylase

Abstract: ■ AbstractChronic exposure to high levels of free fatty acids impairs beta-cell function (lipotoxicity). Then basal insulin secretion (BIS) is increased and glucose-stimulated insulin secretion (GSIS) is inhibited. Acetyl CoA carboxylase (ACC) acts as the sensor for insulin secretion in pancreatic beta-cells in response to glucose and other nutrients. Stevioside (SVS), a diterpene glycoside, has recently been shown to prevent glucotoxic effect by regulating ACC activity. The aim of this study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…To assess if specific Stevia extract components were responsible for this protective effect, INS-1E, treated with palmitate, were exposed to stevioside only. This main stevia component has been shown to ameliorate insulin secretion in INS-1E cells exposed to palmitate or high glucose concentrations by different mechanisms [ 27 , 28 ]. However, in our study, we did not observe any evidence of protection by stevioside alone against palmitate-induced beta-cell death, suggesting that the improvement of beta-cell survival is likely due to combinations of Stevia components or the phytocomplex in toto .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess if specific Stevia extract components were responsible for this protective effect, INS-1E, treated with palmitate, were exposed to stevioside only. This main stevia component has been shown to ameliorate insulin secretion in INS-1E cells exposed to palmitate or high glucose concentrations by different mechanisms [ 27 , 28 ]. However, in our study, we did not observe any evidence of protection by stevioside alone against palmitate-induced beta-cell death, suggesting that the improvement of beta-cell survival is likely due to combinations of Stevia components or the phytocomplex in toto .…”
Section: Discussionmentioning
confidence: 99%
“…These effects are generally thought to be due to steviol glycosides, the molecules that confer sweet flavor to Stevia extracts, although also the non-sweetener fraction might display insulinotropic effects [22]. More than 30 steviol glycosides have been detected in Stevia leaves [23], but the most abundant are stevioside, rebaudioside A and rebaudioside C. In literature, there are studies regarding the action of stevioside in stimulating insulin secretion, both in-vitro and invivo [24][25][26][27][28][29][30][31][32]. No data are currently available on the possible protective effects of Stevia extracts on pancreatic beta cells upon prolonged exposure to certain free fatty acids, also in relation to Stevia secondary metabolites -mainly steviol glycosides, polyphenols, and flavonoids-and their related antioxidant and ROS-scavenging activities.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that, during lipotoxicity, the glycosylated form of ISV, Stevioside, counteracts the impaired insulin secretion from both rat islets and INS-1E cells [19]. Stevioside was able to lower blood glucose in type 2 diabetic subjects [20] and in a non-obese animal model of type 2 diabetes i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies showed that steviol glycosides can stimulate insulin secretion from isolated pancreatic islet cells, up-regulate key genes controlling insulin secretion and have effects on insulin signalling and release (Jeppesen et al, 1996(Jeppesen et al, , 2000(Jeppesen et al, , 2003Costa et al, 2003a;Xiao and Hermansen, 2005;Chen et al, 2006aChen et al, , 2006bChen et al, , 2006cNakamura et al, 2003;Yamamoto et al, 1985) as summarised in Appendix V-I.…”
Section: In Vitro Studiesmentioning
confidence: 99%